2012
DOI: 10.4103/0019-557x.99916
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, protective factors and violence among male adolescents: A comparison between urban and rural school students in West Bengal

Abstract: A cross-sectional study was conducted among 199 (104 urban, 95 rural) male students of classes VIII and IX, of two schools, in urban and rural areas of West Bengal to compare the prevalence of protective factors, mental health issues, and violence among the urban and rural adolescents using a self-administered questionnaire. Higher proportion of urban students than rural (67.3% vs. 62.5%) reported that their guardians understood their problems. Mental health issues like loneliness (17.3% vs. 9.8%), worry (17.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 0 publications
4
50
1
Order By: Relevance
“…These results are in line with a study by Samanta et al [45] where rural living appeared protective against development of mental health issues among male adolescents (13-15 years), as well as with an earlier study in New Zealand, where adolescents from larger population centers reported more life event stresses than those from smaller centers [46]. The mechanisms underlying these region-related differences in psychosomatic health cannot be revealed by the current study.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with a study by Samanta et al [45] where rural living appeared protective against development of mental health issues among male adolescents (13-15 years), as well as with an earlier study in New Zealand, where adolescents from larger population centers reported more life event stresses than those from smaller centers [46]. The mechanisms underlying these region-related differences in psychosomatic health cannot be revealed by the current study.…”
Section: Discussionsupporting
confidence: 93%
“…After retrieving and evaluating the full texts, 28 articles did not meet our criteria. At the end of the screening process, 13 articles met all the inclusion and exclusion criteria and were recruited in this systematic review (Anil et al, 2016;Bhogle, 1991;Grover et al, 2019Grover et al, , 2018Malhotra et al, 2019;Mishra et al, 2013;Nayyar and Singh, 2011;Ninan and Gopinath, 2013;Samanta et al, 2012;Shettar et al, 2017;Singh and Mishra, 2009;Susheela et al, 2018;Upmanyu et al, 1994).…”
Section: Study Selectionmentioning
confidence: 99%
“…Most (n = 4) studies were conducted in Karnataka (Anil et al, 2016;Ninan and Gopinath, 2013;Shettar et al, 2017;Susheela et al, 2018), followed by Punjab (n = 3) Nayyar and Singh, 2011;Upmanyu et al, 1994), Andhra Pradesh (n = 2) (Bhogle, 1991;Mishra et al, 2013), Delhi (n = 1) (Singh and Mishra, 2009), Haryana (n = 1) (Malhotra et al, 2019), and West Bengal (n = 1) (Samanta et al, 2012). A study by Grover et al included participants from multiple states of India (Grover et al, 2018).…”
Section: Study Characteristics and Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations